Different Effects of Vascular Aging on Ischemic Predisposition in Healthy Men and Women. Issue 6 (December 2018) - Namasivayam, Mayooran; McEniery, Carmel M.; Wilkinson, Ian B.; Yasmin,; Cockroft, John R.; McDonnell, Barry J.; Adji, Audrey; O'Rourke, Michael F.
Abstract : Invasive studies of the twentieth century showed the value of aortic pressure-time integrals as markers of myocardial oxygen demand and supply. More recent studies have used these concepts to evaluate the mechanisms of ischemic predisposition using noninvasive arterial tonometry in cardiology outpatients. We sought to evaluate the spectrum of myocardial oxygen demand and supply in a large cross-sectional community sample of healthy volunteers and identify the roles of age, sex, and wave reflection. Arterial tonometry was performed in 3682 healthy volunteers. Measures of systolic and diastolic pressure-time integrals and their ratio in addition to cardiac ejection duration were determined and analyzed by age and sex. Multiple regression analyses were performed to identify the mechanisms underlying observations, while controlling for confounders (heart rate, height, weight, and mean pressure). In a healthy cohort, older women more than men ( P <0.001) had unfavorable myocardial oxygen supply:demand ratios because of differing effects of vascular aging. Abstract : Supplemental Digital Content is available in the text.